2015
DOI: 10.21273/hortsci.50.5.676
|View full text |Cite
|
Sign up to set email alerts
|

End-of-production Supplemental Lighting with Red and Blue Light-emitting Diodes (LEDs) Influences Red Pigmentation of Four Lettuce Varieties

Abstract: Under low-light greenhouse conditions, such as those found in northern latitudes, foliage of red leaf lettuce (Lactuca sativa L.) varieties is often green and not visually appealing to consumers. Our objective was to quantify the effect of end-of-production (EOP; prior to harvest) supplemental lighting (SL) of different sources and intensities on foliage color of four red leaf lettuce varieties, ‘Cherokee’, ‘Magenta’, ‘Ruby Sky’, and ‘Vulcan’. Plants were finished under green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
1
38
1
1
Order By: Relevance
“…Compared with no EOP SL (control), RCC of geranium was significantly higher under LED EOP SL delivering 100 mmol · m -2 · s -1 . Similarly, Owen and Lopez (2015) reported 14 d of EOP SL delivering 100 mmol · m -2 · s -1 provided by 100:0, 0:100, or 50:50 red:blue light, resulted in increased RCC from 29.6 to 32.8 and 26.5 to 29.0 for lettuce 'Cherokee' and 'Ruby Sky' plants, respectively, compared with the control.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Compared with no EOP SL (control), RCC of geranium was significantly higher under LED EOP SL delivering 100 mmol · m -2 · s -1 . Similarly, Owen and Lopez (2015) reported 14 d of EOP SL delivering 100 mmol · m -2 · s -1 provided by 100:0, 0:100, or 50:50 red:blue light, resulted in increased RCC from 29.6 to 32.8 and 26.5 to 29.0 for lettuce 'Cherokee' and 'Ruby Sky' plants, respectively, compared with the control.…”
Section: Resultsmentioning
confidence: 82%
“…For fountain grass, regardless of EOP SL source, RCC significantly increased up to 14 d after exposure to EOP SL; however, an additional 7 d (21 d) of exposure to EOP SL resulted in no significant differences ( respectively, when fountain grass was finished under 70 mmol · m -2 · s -1 delivered from a HPS lamp. Owen and Lopez (2015) also reported that an additional 2 d (from 5 to 7 d) of 50:50 red:blue EOP SL delivering 100 mmol · m -2 · s -1 did not significantly influence RCC of lettuce 'Vulcan' plants. However, in the present study, increasing proportions of blue light significantly increased RCC.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…2, 3). Furthermore, red pigmentation of lettuce leaves is a key component that influences consumer perception of product quality, as it is typically associated with higher anthocyanin content in the foliage (Gazula et al, 2007; Owen and Lopez, 2015; Ryder, 1999). When comparing results for the lowest and highest DLI evaluated in our study, anthocyanin content increased with increasing DLI by 4100% in Experiment 2, and by 1525% in Experiment 3.…”
Section: Resultsmentioning
confidence: 99%